Experimental taphonomy of freshwater diatoms: discriminating between chemical and physical causes of frustule fragmentation - Hassan, Gabriela Susana (2021)
Frustulefragmentation is one of the major taphonomic factors affecting diatompreservation in Pampean shallow lakes. This has been demonstrated both bycontemporary and fossil taphonomic studies, although little is known about thecauses of frustule breakage and its environmental significance. Field studiesalong modern environmental gradients showed a low but significant correlationbetween dissolution and fragmentation, suggesting that debilitation of thefrustule by silica dissolution can be the cause of diatom fragmentation.Reworking of sediments by wind action have also be suggested as a possibleexplanation for the observed fragmentation patterns. To evaluate the relativeimportance of chemical and physical causes of diatom fragmentation, three laboratoryexperiments were conducted to test for 1) the effect of physical agitation, 2)the effect of chemical dissolution, and 3) the joint effect of both variableson diatom fragmentation. Physical agitation was simulated by subjecting diatomsamples to lineal shaking at 250 rpm during 30 days. Chemical dissolution wastested by mixing diatom assemblages with solutions of different concentrationsof NaCl and NaHCO3, and pH 10 during 20days. The joint effect of both processes was tested by diluting diatomassemblages in salt solutions and subjecting them to agitation during 20 daysat 250 rpm. In all cases, aliquots of each assemblage were sampled at initialand final experimental times and taphonomically analyzed through theapplication of fragmentation and dissolution indices. Significant differencesin fragmentation indices were observed both in dissolution alone and combinedexperiments, but no differences were found in the agitation alone essay. In allcases, dissolution and fragmentation indices were correlated, suggesting acausal relationship among them. Overall, our results suggest that the debilitationof the diatom frustule by chemical dissolution may be the main cause of theobserved fragmentation patterns in surface sediments of Pampean shallow lakes.